Soda, clay, and fire - Nichols, Gail. (Westerville, OH American Ceramic Society, 2006)
A comprehensive detailed, artistic approach to the art and technique of soda firing in contemporary ceramics.
Soda -- What is soda? -- How is soda introduced to a kiln? -- Differences between salt glaze and soda glaze -- Aesthetic applications -- Chris Staley -- Val Cushing -- John Chalke -- Ruthanne Tudball -- Val Nicholls -- Jeff Oestreich -- Brad Schwieger -- John Glick -- Victoria Christen -- And what about the environment? -- Clay -- Developing and working with slips -- Choosing a clay body -- Developing high alumina clay bodies -- Roles of clay body components in color development -- Fire -- Kiln design -- Refractories -- Wadding -- Liner glazes -- Firing strategies -- Bisque stage -- Bisque to stoneware (Cone 06-8/9) -- Soda introduction -- Soak -- Cool -- Monitoring the progress of the firing -- What is an oxygen probe and how does it work? -- Draw rings -- Kiln log -- How much soda? Fuels -- Interchanging salt and soda -- Health and safety -- Painting with fire -- Test kiln -- A strategy for firing experiments -- Project 1: Investigating the effects of a reducing atmosphere during stages of firing and cooling -- Project 2: Investigating the effects of lengthening the firing and cooling stages -- Developing a decorative palette -- Creative kiln loading: placing and wadding pots for decorative effects -- Post-firing treatment -- Using water vapor in the kiln atmosphere -- Creative cooling -- Beyond materials and process -- Quest for a new aesthetic -- Making processes -- Uncertainty and intuition -- where to next -- Appendix: Health and safety precautions.
Keywords: Glazing (Ceramics).; Glazes; Pottery craft; Glazes -- Formulae; Glazing (Ceramics) -- Technique; Glasur; Keramik